The Effect of Capital Structure and Profitability on Firm Value with Dividend Policy as A Moderating Variable - Monica Tasya Selvia; Desmy Riani; Diah Yudhawati (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2026)
The objective of this research is to determine how capital structure and profitability dictate firm value, alongside evaluating the moderating function of dividend policy among F&B enterprises operating on the IDX throughout the 2019–2023 period. The study specifically maps out whether dividend policy reinforces or diminishes the pathways connecting capital mix and profitability to overall corporate value. This quantitative study relied on purposive sampling to gather a research matrix consisting of 20 companies and 100 firm-year observations across five years. The underlying secondary data, including annual reports and fully audited financial records, were retrieved from individual corporate web portals and the official IDX platform, compiled through structured documentation techniques. Hypotheses were verified through panel data regression using a Moderated Regression Analysis (MRA) model. The statistical outcomes conclude that: (1) Capital Structure has no significant effect on Firm Value, (2) Profitability has a positive and significant effect on Firm Value, (3) Dividend Policy is unable to moderate the effect of capital structure on firm value, (4) Dividend Policy is able to moderate the effect of profitability on firm value in a weakening direction